Memperkuat Komunitas Melalui Program Pengelolaan Sampah untuk Keberlanjutan di Desa Suka Makmur - Muhammad Arie Firmansyah; Putri Ana; Putri Cahya Novebriani; Putri Kartika; Putri Suway Batur Roja’i; Surti Lestari; Rahmatullah Rahmatullah (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The village of Suka Makmur faces challenges in waste management, where waste is often not sorted and potentially poses environmental impacts. The Waste Bank programme has been reactivated to address this issue by implementing the 3R principles (Reduce, Reuse, Recycle) and providing economic benefits to the community. This research employed a participatory approach, involving residents in an initial survey, waste sorting training, and the operation of the Waste Bank. Continuous education was provided to ensure the community understands the importance of waste management and the economic potential of collected waste. The results indicate increased community participation, reduced waste disposal volumes, and economic benefits for residents. The Waste Bank has successfully raised environmental awareness and empowered the community to manage waste sustainably.